2022
DOI: 10.1029/2022ea002234
|View full text |Cite
|
Sign up to set email alerts
|

A Study in Blue: Secondary Copper‐Rich Minerals and Their Associated Bacterial Diversity in Icelandic Lava Tubes

Abstract: Cave environments on Earth have long provided shelter to a variety of organisms, from microbes to humans. Though their scales of interest differ vastly, these two examples have sought the same comfort from caves: a stable and sheltered environment, protected from the woes of the surface world. Since the discovery of lava caves on Mars (see Sauro et al., 2020 for a review), they have become of renewed interest as targets for human shelter in future missions, as well as areas of astrobiological interest, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…The observation of chrysocolla amorphous phases was supported by the SEM–EDX image data (Figure B), wherein several copper-rich particles, copper, silicon, and aluminum, as the main elements of chrysocolla, could be found together (i.e., particles with light blue color in Figure B). The EDX spot mode was used to acquire semiquantitative elemental composition from those copper-rich particles, and the average copper:silicon:aluminum mole ratio was calculated to be 1.7:1.5:0.12, which are similar to typical chrysocolla values reported in previous studies. Aside from chrysocolla, copper was also present in the form of malachite (21 wt %), a secondary carbonate copper ore, that was identified together with talc (5 wt %) and muscovite (4 wt %) as the other dominant minerals. Chemical analysis by ICP-OES showed that copper was the main element in the material, corresponding to almost 38 wt %, followed by silicon (12 wt %), while magnesium, iron, and aluminum were present in lower concentrations (Table ).…”
Section: Resultssupporting
confidence: 64%
“…The observation of chrysocolla amorphous phases was supported by the SEM–EDX image data (Figure B), wherein several copper-rich particles, copper, silicon, and aluminum, as the main elements of chrysocolla, could be found together (i.e., particles with light blue color in Figure B). The EDX spot mode was used to acquire semiquantitative elemental composition from those copper-rich particles, and the average copper:silicon:aluminum mole ratio was calculated to be 1.7:1.5:0.12, which are similar to typical chrysocolla values reported in previous studies. Aside from chrysocolla, copper was also present in the form of malachite (21 wt %), a secondary carbonate copper ore, that was identified together with talc (5 wt %) and muscovite (4 wt %) as the other dominant minerals. Chemical analysis by ICP-OES showed that copper was the main element in the material, corresponding to almost 38 wt %, followed by silicon (12 wt %), while magnesium, iron, and aluminum were present in lower concentrations (Table ).…”
Section: Resultssupporting
confidence: 64%
“…They are widespread in some extreme environments on Earth, such as deep-sea hot springs, volcanic craters and geothermally active areas. 117 While the study of hyperthermophilic bacteria began in the late 1960s and early 1970s, the 1980s was an important period of research, 118 in which in-depth studies of activity mechanisms revealed how these microorganisms survive and proliferate in high-temperature environments. With the development of molecular biology and genomics in the 1990s, scientists began to utilize molecular techniques to study in depth the genome of hyperthermophiles and their mechanisms of gene expression regulation.…”
Section: Application Of Microbial Agents In Compostingmentioning
confidence: 99%
“…The data supplement to this work is accessible at https://public.yoda.uu.nl/geo/UU01/I32Z95.html, https://doi. org/10.24416/UU01-I32Z95 (Kopacz, 2022). In addition, the raw genetic sequences for this study have been deposited in the European Nucleotide Archive (ENA) at the European Molecular Biology Laboratory-European Bioinformatics Institute (EMBL-EBI) under accession number PRJEB51902 (www.ebi.ac.uk/ena/browser/ view/PRJEB51902) (Klarenberg, 2022).…”
Section: Data Availability Statementmentioning
confidence: 99%